(untitled) - Serway, Raymond A. (Philadelphia, 1982)
The country's bestselling calculus-based physics text, recognized by over 700 schools for its currency, accuracy, and clarity, has received a carefully crafted revision. Its strong problem solving approach, incorporating new intermediate and challenging problems, innovative spreadsheet problems, and ground-breaking conceptual problems with reasoning statements teach students how to think through physical examples as opposed to plugging numbers into formulas. Complementing this unsurpassed textbook is an exceptional ancillary package, complete with interactive multimedia support.
Keywords: Physics,Vật lý